Removal of a Broken Instrument from a Tooth with Apical Periodontitis Using a Novel Approach - Heydari, Azar; Rahmani, Mona; Heydari, Mostafa (Iranian Endodontic Journal, 2016)
Instrument breakage during treatment can lead to serious complications and carries the risk of treatment failure. When a file breaks in the canal, bypassing or removal can be difficult and the long-term prognosis of the tooth may be compromised. Sometimes surgery may be indicated for removal of the broken segment. Often some part of the root cannot be cleaned because of blockage by the broken file. This report presents a specific approach in non-surgical removal of a broken file from a maxillary lateral incisor with a buccal sinus tract and a broken instrument in the apical third which was partially over extended into the periapical lesion. The broken file was accessed through the sinus tract and pushed into the canal. The canal was cleaned and shaped, filled with mineral trioxide aggregate (MTA). Conclusion: A sinus tract can be a specific path to reach the root tip and get access to remove the foreign materials pushed beyond the root canal space. Keywords: Apical Surgery; Broken Instrument; Nonsurgical Retreatment